The Dynamics of the Decline of Madrasah Diniyah Students: Curriculum Challenges, Family Economy, and the Influence of Digital Technology - Ayu Nurul Hikmah; Ubaidillah; Sefi Islamiya Pasha; Tsalatsa Fajriyah (Social Journal of Studies in Education, 2026)
This study specifically conducts a comprehensive analysis of the critical phenomenon of declining enrollment in Madrasah Diniyah schools within Islamic foundations in the Tlogosari Wetan district of Semarang City, Indonesia, from the perspective of contemporary Islamic education. Adopting a qualitative approach with a phenomenological design, data were collected through unstructured interviews, participant observation, and document analysis in Pedurungan Subdistrict, then analyzed using the Miles and Huberman interactive model to ensure empirical validity. Key findings reveal the decline in student enrollment as a multidimensional phenomenon, driven by three dominant, mutually interacting factors: the economic priorities of urban families that prioritize formal education, a stagnant curriculum that is irrelevant to Generation Z, and the penetration of digital technology that diverts children’s interests. These factors exacerbate the marginalization of madrasahs, triggering operational and humanitarian crises such as budget deficits, limited facilities, and the erosion of teachers’ welfare, which significantly reduce the quality of education. Although administrators have implemented digital curriculum innovations, schedule adjustments, and strategic collaborations, these efforts are hindered by limited human and financial resources. Therefore, an urgent holistic intervention is needed that integrates financial management, teacher protection, and sustainable educational methodology transformation through government-community collaboration. The findings of this study provide an empirical basis for strategic policies that not only aim to increase the number of santri but also strengthen the operations and core values of Islamic education, adapting them to urban dynamics, in order to ensure the continued existence of these non-formal institutions in the future.